Inkluzje w przestrzeni. Esej o uzdrowiskach - Agnieszka Czyżak (Zagadnienia Rodzajów Literackich)
The main aim of the article is to show spas as specific places in geographical and cultural space, called in this text “inclusions”. This geological term is used to bring an awareness to the difference which defines their essence. Contemporary literature reveals the otherness of spas. The article contains an analysis of autobiographical confessions written by Monika Sznajderman (Pusty las, published 2018), Ilona Witkowska (Biuro Usług Kuracjuszy, 2019) which shows the mechanism of settling the places chosen for living. On the other hand novels written nowadays by Olga Tokarczuk (Empuzjon, published 2022) and Joanna Bator (Gorzko, gorzko, 2022) also recognize the processes of formation of the cultural difference of spas and the conditions of their duration over time. Finally, in consideration there appears an interpretation of a poem written by Tadeusz Różewicz (Grypa w Krynicy, written 1984) which enables a return to the era of PRL (Polish People Republic) as well as recognizing the universal dimension of the spa experience